Congregation perception towards the roles and responsibilities of the mosque Imams in Terengganu Malaysia - Rohaizan, Baru; Fauzilah, Salleh; Wan Fajrulhisyam, Wan Abdullah; Jamalluddin, Hashim (2011)
This paper attempted to review the congregants’ perception of the roles and responsibilities of Imam which rely on three dimensions: the official duties, the administration of the mosque and the community services. A comprehensive survey in the entire state of Terengganu has been outlined with several major goals; to identify the roles and responsibilities of an Imam, to analyses the perception of the roles and responsibilities of the Imam from the aspect of official duties, the administration of mosques, and also the community services